Apakah RW Secara Mandiri Mampu Menangani Sampah Tanpa Bantuan PEMDA? - Badruzzaman, Farid H; Purwanda, Eka; Harahap, Erwin; Ibrahim, Salawat Fatih; Erfiyana, Evi (Jurnal Online Manajemen ELPEI, 2025)
This study aims to determine whether the Community Units (RW) are independently able to handle waste without assistance from the Regional Government. Waste management in Bandung Regency is becoming increasingly complex with the increasingly full capacity of the Sarimukti Final Waste Disposal Site (TPA), West Bandung Regency. This has caused the Regional Government together with the West Java Provincial Government to take strategic steps to reduce the volume of waste sent to the TPA. One of the main strategies that is being actively carried out is to encourage the community to start sorting waste from the source, especially at the household level. In addition, the Bandung Regency Government has also introduced the "Zero Food Waste" program. Data were obtained through surveys, interviews, and direct observations in RW 12, Cimenyan District. The conclusion of this study is that the Community Units (RW) have not been able to manage waste independently without assistance from the Regional Government. The results of the study are expected to help the Regional Government (Pemda) design a more effective waste management strategy